The politics of bureaucratic corruption in post-transitional Eastern Europe - Zaloznaya, Marina (Cambridge studies in law and society, 2017)
Introduction -- Beyond transition: political turnover and bureaucratic corruption in hybrid regimes -- The secret life of universities in post-Soviet Ukraine -- Fear and transparency in the universities of post-Soviet Belarus -- High political turnover and cross-organizational variation in corruption in post-Soviet Ukraine -- Low political turnover and cross-sectoral variation in corruption in post-Soviet Belarus -- Conclusion